Heat shock proteins and heat shock factor 1 in carcinogenesis and tumor development: an update - Ciocca, Daniel Ramon (2013)
Heat shock proteins (HSP) are a subset of the molecular chaperones, best known for their rapid and abundant induction by stress. HSP genes are activated at the transcriptional level by heat shock transcription factor 1 (HSF1). During the progression of many types of cancer, this heat shock transcriptional regulon becomes co-opted by mechanisms that are currently unclear, although evidently triggered in the emerging tumor cell. Concerted activation of HSF1 and the accumulation of HSPs then participate in many of the traits that permit the malignant phenotype. Thus, cancers of many histologies exhibit activated HSF1 and increased HSP levels that may help to deter tumor suppression and evade therapy in the clinic. We review here the extensive work that has been carried out and is still in progress aimed at (1) understanding the oncogenic mechanisms by which HSP genes are switched on, (2) determining the roles of HSF1/HSP in malignant transformation and (3) discovering approaches to therapy based on disrupting the influence of the HSF1-controlled transcriptome in cancer.